Penerapan Strategi Pembelajaran Aktif Tipe Inquiring Mind Want to Know untuk Meningkatkan Pemahaman Konsep dan Pemecahan Masalah Matematis - Yulia, Yulia; Markis, Tessy Marzalfa (Math Educa Journal, 2017)
The purpose of this study was to determine that the conceptual understanding of math and problem solving skill of students taught using the application of active learning strategies types Inquiring Mind Want to Know better than the conceptual understanding of math students taught using conventional strategy. This research is a quasi-experimental research with the design of randomized control group only design. The populations in this study were five classes of students of grade VII SMPN 35 Padang (165 students). The choice of class random sampling (random data retrieval). Classes are chosen as experimental class is a class VII.4 and control class is the class VII.5.  Data were taken from the results of final test is a test essay from each class. Based on the data analysis of research obtained that the understanding of math concepts and problem solving experimental class students is higher than the control class. This is evident from the average value of the test understanding of concepts and mathematical problem solving experimental class students is 76,45 while the average grade control is 63,27. Hypothesis testing using t-test, obtained tcalculate > ttable   (1,72 > 1,65) with a 95% confidence level, the hypothesis is accepted. So it can be concluded that the understanding of math concepts and problem solving students who apply active learning strategies types “Inquiring Mind Want to Know” better than on understanding math concepts and problem solving students using conventional teaching in class VII SMPN 35 Padang.Keywords: Active learning strategies types Inquiring Mind Want to Know, understanding math concepts, and problem solving